Unusual hierarchical structures of micro-injection molded isotactic polypropylene in presence of an in situ microfibrillar network and a β-nucleating agent. Issue 54 (13th June 2015) - Zhao, Zhongguo; Yang, Qi; Kong, Miqiu; Tang, Dahang; Chen, Qianying; Liu, Ying; Lou, Fangli; Huang, Yajiang; Liao, Xia
<x xml:space="preserve">Abstract</x> The morphological development of iPP in presence of an in situ microfibrillar network and a β-nucleating agent under micro-injection molding.